3-D elasto-plastic large deformations: IGA simulation by Bézier extraction of NURBS. (June 2017) - Lai, Wenjiang; Yu, Tiantang; Bui, Tinh Quoc; Wang, Zhiguo; Curiel-Sosa, Jose L.; Das, Raj; Hirose, Sohichi
Highlights: Numerical analysis of 3-D elasto-plastic large deformations is presented. Isogeometric analysis based on Bézier extraction of NURBS is extended to 3-D elasto-plastic large deformation. The Bézier extraction operator can integrate isogeometric analysis into the existing finite element codes. Higher accuracy is obtained as compared with that of finite element method. Abstract: This paper is devoted to the numerical simulation of elasto-plastic large deformation in three-dimensional (3-D) solids using isogeometric analysis (IGA) based on Bézier extraction of NURBS (non-uniform rational B-splines), due to some inherently desirable features. The Bézier extraction operation decomposes the NURBS basis functions into a set of linear combination of Bernstein polynomials and a set of C 0 -continuity Bézier elements. Consequently, the IGA based on Bézier extraction of NURBS can be embedded in existing FEM codes, and more importantly, as have been shown in literature that higher accuracy over traditional FEM can be gained. The main features distinguishing between the IGA and FEM are the exact geometry description with fewer control points, high-order continuity, high accuracy. Unlike the standard FEM, the NURBS basis functions are capable of precisely describing both geometry and solution fields. The present kinematic is based on the Total Lagrange description due to the elasto-plastic large deformation with deformation history. The results for the distributions of displacements, von Mises stress, yielded zones, and force-displacement curves are computed and analyzed. For the sake of comparison of the numerical results, the same numerical examples have additionally been computed with the FEM using ABAQUS. IGA numerical results show the robustness and accuracy of the technique.